Edukasi Kesehatan tentang Terapi Komplementer pada Ibu Hamil dengan Nyeri Punggung di Puskesmas Putri Ayu Tahun 2024 - Sulistiawati, Ira; Tiwi, Laida Sanilpa (Jurnal Abdimas Kesehatan (JAK), 2025)
Complementary therapy is a form of healing that is based on various modality systems in health practices supported by theory and belief. Currently, many people are switching from modern medicine to complementary medicine. Traditional health services or what are now called complementary services utilize biomedical and biocultural sciences, complementary treatment or care methods can be in the form of skills using manual techniques, energy therapy and thought therapy. The influence of the body's metabolic system and the musculoskeletal system more or less affects the mother's body during pregnancy. Changes that occur include lower back pain. Women during their pregnancy need time to adapt to the various changes that occur in themselves. Midwifery care is carried out by combining conventional and complementary midwifery services, and has become an important part of midwifery practice. Complementary therapy in midwifery care can be used as a means to support the normal process of pregnancy and birth and to respect women's autonomy. Health education about complementary therapy in pregnant women with back pain, counseling methods when pregnant women carry out mother classes in the work area of ​​the Putri Ayu Health Center, Jambi City. This activity was carried out in conjunction with the community practice of the Midwifery profession students of Stikes Baiturrahim Jambi.